Preparation and evaluation of poly lactic acid antioxidant packaging films containing thyme, rosemary and oregano essential oils. - Zeid, Amr Mostafa (AUC Knowledge Fountain, 2015)
Protecting foods from oxidation for appreciable amounts of time is becoming a major challenge for the food industry. Lipid containing foods are the most susceptible types of food to oxidation. In the present research study, thyme, rosemary and oregano essential oils were incorporated into PLA to generate antioxidant active packaging films based on the antioxidant activity of the used essential oils. Antioxidant activity of pure essential oils as well as film extracts were assessed by the DPPH method to ensure their efficiency. The antioxidant effect of prepared active films was also evaluated in contact with minced trout fish meat by using the TBA method. Mechanical properties, oxygen permeability and migration properties of the films were tested. Thyme essential oil showed a Radical Scavenging Activity (RSA) of 84.57% in the DPPH test, while rosemary and oregano had a RSA of 87.92% and 87.73% respectively at 10000 ppm concentration. Antioxidant activity of methanol extracts from thyme, rosemary and oregano films were between 4% and 6% lower than that shown by pure essential oils at the same concentration. TBA test results showed a decrease in degree of oxidation of minced fish packaged in thyme active film by 10.8% as compared to that packaged in control film. While Rosemary active film reduced oxidation by 20.3%. Oregano active film caused the highest decrease in oxidation by 47.9%. PLA films prepared by the solvent casting method containing thyme, rosemary or oregano essential oils may be used as antioxidant active packaging materials.